LA COMUNICACIÓN INTERNA Y LA PROMOCIÓN DE LA SALUD. ESTUDIO DE CASO EN MADRID SALUD. - Bustamante Ospina, Edilson (Hacia la Promoción de la Salud)
Objective: To describe the incidence of internal communication in the work of health promotion. Materials and Methods: A descriptive and exploratory research used the case study through triangulation techniques (interviews, content analysis and survey) for the collection and analysis of information between February and August 2012 in Madrid Salud in six of its centers. Interviews were administered to 8 civil servants in senior and middle positions in the business and content analysis of recent reports of the organization was carried out; 87 surveys were applied to employees of six Health Centers belonging to Madrid Salud. Results: Internal communication is positively assessed as a factor that enhances the development of actions in health promotion through work from six variables: Identification, Information, Instruction, Integration, Image and Research. Conclusions: An internal communication strategy that seeks to enhance the work of health promotion must include: the search for Identification of employees managing the philosophy that health promotion involves; provision of useful and timely Information on the organization and on health promotion; Instructional support for staff especially in the developement of communication skills and teamwork; promotion of the integration of the employees to health promotion processes; working for the creation of a positive image of the organization and employees; and encouragement of research of internal communication processes to improve the strategy and its functions.